Macrophage Migration Inhibitory Factor for the Early Prediction of Infarct Size. Issue 5 (4th October 2013) - Chan, William; White, David A.; Wang, Xin‐Yu; Bai, Ru‐Feng; Liu, Yang; Yu, Hai‐Yi; Zhang, You‐Yi; Fan, Fenling; Schneider, Hans G.; Duffy, Stephen J.; Taylor, Andrew J.; Du, Xiao‐Jun; et al.
Abstract : Background: Early diagnosis and knowledge of infarct size is critical for the management of acute myocardial infarction (MI). We evaluated whether early elevated plasma level of macrophage migration inhibitory factor (MIF) is useful for these purposes in patients with ST‐elevation MI (STEMI). Methods and Results: We first studied MIF level in plasma and the myocardium in mice and determined infarct size. MI for 15 or 60 minutes resulted in 2.5‐fold increase over control values in plasma MIF levels while MIF content in the ischemic myocardium reduced by 50% and plasma MIF levels correlated with myocardium‐at‐risk and infarct size at both time‐points ( P <0.01). In patients with STEMI, we obtained admission plasma samples and measured MIF, conventional troponins (TnI, TnT), high sensitive TnI (hsTnI), creatine kinase (CK), CK‐MB, and myoglobin. Infarct size was assessed by cardiac magnetic resonance (CMR) imaging. Patients with chronic stable angina and healthy volunteers were studied as controls. Of 374 STEMI patients, 68% had elevated admission MIF levels above the highest value in healthy controls (>41.6 ng/mL), a proportion similar to hsTnI (75%) and TnI (50%), but greater than other biomarkers studied (20% to 31%, all P <0.05 versus MIF). Only admission MIF levels correlated with CMR‐derived infarct size, ventricular volumes and ejection fraction (n=42, r=0.46 to 0.77, all P <0.01) at 3 day and 3 months post‐MI. Conclusion: Plasma MIF levels are elevated in a high proportion of STEMI patients at the first obtainable sample and these levels are predictive of final infarct size and the extent of cardiac remodeling.